2019
DOI: 10.1103/physrevphyseducres.15.020126
|View full text |Cite
|
Sign up to set email alerts
|

Calculus-enhanced energy-first curriculum for introductory physics improves student performance locally and in downstream courses

Abstract: Here we demonstrate the benefits of a new curriculum for introductory calculus-based physics that motivates classical mechanics using a modified version of Hamiltonian mechanics. This curriculum shifts the initial focus of instruction away from forces and the associated vector mathematics, which are known to be problematic for students, to the scalar quantity energy, which is more closely aligned with their previously established intuition, and associated differential and integral calculus. We show that implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Since we implemented a new curriculum for PHSX 211 in the Spring 2015 semester [26], we analyzed the performance of only students completing PHSX 211 between the Spring 2015 semester and the Spring 2019 semester; the total course enrollment for these semesters is 727 students. These data include seven semesters in which ALPaCA grading was not used (635 students between Spring 2015 and Spring 2018) and two semesters in which it was used (182 students in Fall 2018 and Spring 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since we implemented a new curriculum for PHSX 211 in the Spring 2015 semester [26], we analyzed the performance of only students completing PHSX 211 between the Spring 2015 semester and the Spring 2019 semester; the total course enrollment for these semesters is 727 students. These data include seven semesters in which ALPaCA grading was not used (635 students between Spring 2015 and Spring 2018) and two semesters in which it was used (182 students in Fall 2018 and Spring 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Further separate investigation of these data also allowed us to quantify the relative difficulty of each content area in PHSX 211. We found that students struggle with force-based mechanics more than energy-based mechanics [26], and that quantitative problem solving with momentum presents the largest difficulty. Taken together, these results are consistent with previously published studies [25,35,36,37,45] and also suggest how instruction methods and time might be adjusted to better serve the needs of students.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…One example of this type of introductory course redesign was undertaken by physics professors at the University of Kansas. Rather than beginning the course with the topic of forces, faculty developed a “calculus‐enhanced energy‐first” curriculum because the focus on energy aligned better with many students’ intuitive knowledge of physics and allowed students to develop and apply their calculus skills from the start, leading to better subsequent course outcomes (LeGresley et al., 2019). Embedding academic supports can involve collaboration across programs and meta‐majors and with student services staff that brings supports closer to students and the classroom content they are learning.…”
Section: Guided Pathwaysmentioning
confidence: 99%